Gary buys a 3 1/2 pound bag of cat food every 3 weeks. Gary feeds his cat the same amount of food each day. Which expression can Gary use to determine the number of pounds of cat food his cat eats each year? (1 year = 52 weeks)A. 7/2 x 52/3
B. 7/2 x 3/52
C. 3 ( 1/2 x 3/52
D. 3 ( 1/2 x 52/3 )

Answers

Answer 1
Answer: d is the answer jdjjdjdkdkdkdkdkkdjd

Related Questions

Does it matter term is first and which term is second in a ratio?
The store paid $4.50 for a book and sold it for $7.65. What is the profit as a percent of the cost to the store?
The finances of a group of pet owners were analyzed to determine how much they were spending on their pet(s) each year. A graph of that data is shown: Would (2.5, 8.5) be a realistic solution for the function? Explain.Yes, it is realistic to have 2.5 owners.No, it is not realistic to have 2.5 owners.Yes, it is realistic that owners spend $850 a year on their pet(s).No, it is not realistic that owners spend $850 a year on their pet(s).
9 lb equals how many ounces
Evaluate the expression 10 + (8-4)2 - 2.​

A farmer will divide a 1/4 acre plot of land into three equal-sized sections what will be the size of each section?

Five friends will share equally 1/2 yard if felt for an art project.  How much felt will each friend get?

Answers

1/4:3= 1/4•1/3=1/12acre - size of each section

1/2•1/5=1/10yard
#1) 1/4/3
1/4*1/3
=1/12
#2 1/2/5
1/2*1/5
=1/10

What is the range of possible sizes for side x? _ < x < _

Answers

Answer:

  0.5 < x < 16.5

Step-by-step explanation:

The third side of the triangle must be longer than the difference of the other two sides:

  x > (8.5 -8.0)

  x > 0.5

And it must be shorter than their sum:

  x < (8.5 +8.0)

  x < 16.5

The third side must be in the range ...

  0.5 < x < 16.5

_____

These limits are a direct consequence of the triangle inequality, which requires the sum of the two shortest sides exceed the length of the longest side.

|60| ___ |-60|
>
=
<
fill in the blank

Answers

The inequality ∣60∣≤∣−60∣ holds true. This is because the absolute value of both 60 and -60 is equal to 60.

The expression ∣60∣≤∣−60∣ can be evaluated by calculating the absolute values on both sides. The absolute value of 60 is 60, and the absolute value of -60 is also 60. So, ∣60∣=∣−60∣=60.

Since 60 is equal to 60, the inequality ∣60∣≤∣−60∣ is true. This inequality states that the absolute value of 60 is less than or equal to the absolute value of -60. In this case, since both absolute values are equal, the statement is true. The absolute value function essentially removes the negative sign from a negative number, making it positive, and in this case, the absolute values of 60 and -60 are indeed the same, resulting in a true inequality.

To know more about inequality:

brainly.com/question/28823603


#SPJ3

Answer:

=

Step-by-step explanation:

mod means positive...that's why both are equal 60=60

0.75 turn into a percent

Answers

1. Move the decimal to places to the right.

2. Remove the zero

3. And the answer is 75%

75%, hun! Let us know if you need any more help haha

Simplify x0y-3/x2y-1

Answers

Answer:

For x: We subtract the exponents,

this way. 0 - 2 = -2

For y: We subtract the exponents,

this way. -3 - -1 = -2

x -² y -²

Bonsoir à tous, j'ai besoin d'aide urgemment en maths si possible et merci d'avance. L'exercice est photographié ci-dessus

Answers

m<SAB = 180 - 58,5 = 121,5

180 - 121,5 - 34,1 = 23,4

(sin 121,5)/SB = (sin 23.4)/18,7

SB = (sin 121,5 * 18,7)/(sin 23,4)

SB = 40,15

sin B = h/SB

h = (SB) * sin B

h = 40,15 * sin 35.1

h = 23,1